2019
DOI: 10.1108/jima-12-2017-0143
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the intention of generation M to choose family takaful and the role of halal certification

Abstract: Purpose The purpose of this paper is to investigate the factors that influence the intention to choose family takaful in Pakistan through using theory of reasoned action (TRA) model. While family takaful is not a new financial solution in the market, the main factors that motivate customers to purchase family takaful remain unexplored. To fill this gap, this paper investigated the impact of attitude (ATT), subjective norm (SBN) with the addition of Halal certification (HCT) to predict the behavioral intention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 69 publications
5
39
0
1
Order By: Relevance
“…Firstly, the results of the study indicate that attitude has the strongest influence on Muslims' intention to visit homestays in Sabah. This finding supported earlier studies by Johan et al (2020), Farhat et al (2019), Bashir (2019), Memon et al (2019), Ng et al (2019), Patwary et al (2018), Suki & Salleh (2018), Elseidi (2017), Khan & Azam (2016), Amin et al (2011), Lada et al (2009), Lee & Moscardo (2005), Lam & Hsu (2004) and Chen (1998). In short, Muslims' attitude plays an important role in predicting their intention to visit homestays in Sabah.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Firstly, the results of the study indicate that attitude has the strongest influence on Muslims' intention to visit homestays in Sabah. This finding supported earlier studies by Johan et al (2020), Farhat et al (2019), Bashir (2019), Memon et al (2019), Ng et al (2019), Patwary et al (2018), Suki & Salleh (2018), Elseidi (2017), Khan & Azam (2016), Amin et al (2011), Lada et al (2009), Lee & Moscardo (2005), Lam & Hsu (2004) and Chen (1998). In short, Muslims' attitude plays an important role in predicting their intention to visit homestays in Sabah.…”
Section: Discussionsupporting
confidence: 91%
“…More recently, Johan et al (2020) discovered that a devout Muslim was showing an positive attitude towards Islamic products and services, which later lead them to make purchase action. Similarly, Farhat et al (2019) also reported a positive and significant link between attitude and Muslims' intention to buy Family Takaful in Pakistan. In agreement with those findings, other studies such as Bashir 2019, Memon et al (2019), and Khan & Azam (2016) who were studying the halal-labelled products were also found that there was a positive relationship between attitude and Muslim consumers' purchase intention.…”
Section: The Effect Of Attitude On Intentionmentioning
confidence: 86%
“…With the increasing awareness among the Muslim community these days on the concept of halal, there comes the demand for halal certification system (Marzuki et al , 2012). It is considered vital for the customers who prefer to consume halal products as it provides some level of assurance that the food has been processed and prepared according to Sharia terms and procedures (Farhat et al , 2019). Majority of people think that halal is mainly related to food or food products; however, the truth is that it covers all the aspects of life as a Muslim.…”
Section: Related Studiesmentioning
confidence: 99%
“…A search of the literature showed that previous studies focused more on customer intention to participate in takaful from various factors which included mass media, word of mouth, and subjective norms (Maizaitulaidawati et al, 2016;Farhat et al, 2019), attitude, subjective norm, and perceived behavior (Maizaitulaidawati & Asmak, 2013), perception of takaful operators' performance (Haji Wahab, 2018), and customer beliefs (Bhatti & Md Husin, 2019).…”
Section: Introductionmentioning
confidence: 99%